(untitled) (Journal of Current and Advance Medical Research, 2016)
Background: Ludwigs angina produces a serious morbidity. Objective: The purpose of the present study was to find out the risk factors, treatment response of the antibiotics and complication of the Ludwigs angina, which will help in prevention and management of this potentially dangerous condition. Methodology: A prospective study was carried out from September 2014 to August 2015 at the department of Otolaryngology-Head & Neck surgery of Banghabandhu Sheikh Mujib Medical University (BSMMU), BIRDEM general hospital and DMCH. This study included 30 patients with Ludwigs angina. In this study minimum age, maximum age and mean age were taken. Result: Highest numbers of patients were in the 3rd decade of life. Out of 30 patients, male were 70% and female were 30%. Majority of the patients (76.59%) were from rural area. And the nutritional statuses of the patients were below average. Almost all the patients came with the complaints of neck swelling, pain and fever. Dental infection was the commonest source of infection. Here growth of colony found 76.67% and Streptococci (strep. Viridans) was found in 30% cases. Maximum patients were treated by parental antibiotics with surgical drainage. Eight patients developed complications, and five patients died in this series. Average hospital stays of the patients were 11.2 days. Conclusion: Most of the patients are male with poor socioeconomic class and Streptococci Viridans is the commonest organism. Journal of Current and Advance Medical Research 2016;3(1):16-21